2019
DOI: 10.1186/s43141-019-0003-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro regeneration approaches for restoration of Ceropegia mohanramii—an endemic and critically endangered asclepiad

Abstract: The study aimed to develop an efficient, rapid, and large-scale in vitro regeneration system for propagation, conservation, and restoration of an endemic and critically endangered herb, Ceropegia mohanramii. The cultures were established using nodal explants on Murashige and Skoog’s (MS) medium supplemented with 6-benzylaminopurine (BAP: 1.0 mg/l). Nodal buds cultured on MS medium supplemented with BAP (2.0 mg/l) along with indole-3-butyric acid (IBA, 0.5 mg/l) resulted with production of maximum number of sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Medium supplemented with auxin at low concentrations in combination with cytokinin promote the growth and formation of new shoots, consequently, increasing multiplication rate [29]. Adsul et al [30] reported that nodal buds cultured on MS medium supplemented with 2.0 mg/l BAP in combination with 0.5 mg/l IBA resulted in production of maximum number of shoots (17.1 ± 1.2) of Ceropegia mohanramii. In contrast, Fraternale et al [31] reported high concentration of IBA with BAP (1.5 mg/l) in MS medium was suitable for shoot multiplication of Bupleurum fruticosum.…”
Section: Discussionmentioning
confidence: 99%
“…Medium supplemented with auxin at low concentrations in combination with cytokinin promote the growth and formation of new shoots, consequently, increasing multiplication rate [29]. Adsul et al [30] reported that nodal buds cultured on MS medium supplemented with 2.0 mg/l BAP in combination with 0.5 mg/l IBA resulted in production of maximum number of shoots (17.1 ± 1.2) of Ceropegia mohanramii. In contrast, Fraternale et al [31] reported high concentration of IBA with BAP (1.5 mg/l) in MS medium was suitable for shoot multiplication of Bupleurum fruticosum.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that the in vitro germination protocol developed in this study, despite being more expensive and less simple, is efficient. Furthermore, such in vitro germinated plants could be further used for micropropagation and/or directly planted into its natural habitat; such strategies have been successfully reported for numerous endangered species with medicinal use [ 25 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The shoots grown on BAP and IAA containing media were more vigorous, than those developed in PGR supplementation. A synergistic effect of BAP along with various auxins on bud proliferation and multiple shoot formation has been reported for several plant species including Hemidesmus indicus (Sreekumar et al 2000), Huernia hystrix (Amoo et al 2009), Ceropegia panchganiensis (Chavan et al 2013), and Ceropegia mohanramii (Adsul et al 2019), another members of Apocynaceae. A combination of BAP and KN exhibited symptoms of hyperhydricity and reduced shoot elongation.…”
Section: In Vitro Propagationmentioning
confidence: 94%